Penerapan Model Waterfall dalam Proyek Sistem Informasi Penjualan Komoditas Agribisnis Berbasis Web - Kamal Jumlat; Sendi Trisswandi; Risa Haryani; Sukmawati Anggraeni Putri; Eko Setia Budi (Bulletin of Computer Science Research, 2025)
PT. Cahaya Gunung Permai is a national company operating in the agribusiness sector including planting, breeding, management and marketing. This project aims to develop a web-based agribusiness commodity sales information system for PT. Cahaya Gunung Permai (taniku.co.id), with a focus on increasing efficiency and accessibility in the sales and marketing process of agribusiness products. This system is designed to provide integrated solutions that enable companies to reach a wider market, reduce dependence on intermediaries, and increase profit margins. By utilizing web technology, this system provides a user-friendly platform for users, including inventory management, order processing and real-time reporting features. The project also places great emphasis on data security and user privacy to ensure the protection of sensitive information. Through comprehensive training and technical support, companies are expected to be able to optimize the use of this system. As a result, PT. Cahaya Gunung Permai can increase its competitiveness in the digital-based agribusiness market, with better operational efficiency and access to more in-depth information for strategic decision making. This project is an important step in the company's digital transformation and has the potential to have a significant positive impact on the entire agribusiness value chain.